(untitled) (Journal Of Educational and Psychological Researches, 2024)
The study aims to identify the extent to which the school sports curriculum includes positive trends toward physical and mental health from the point of view of teachers. The researcher applied the descriptive analytical approach, as this approach is appropriate for this type of research. An electronic questionnaire was used as an important tool for data collection to identify the opinions of school sports teachers about the extent to which the school sports curriculum includes trends toward physical and mental health. 223 responses were collected. One of the most important results was the curricular interest in students’ positive participation and cooperation and its keenness to emphasize teaching methods that seek to develop students’ awareness of mental safety through school sports lessons and also with making students feel comfortable and psychologically comfortable through the implementation of applied lessons.